Superoxide dismutase 3 protects mesenchymal stem cells through enhanced autophagy and regulation of FoxO3a trafficking - Agrahari, Gaurav (BMB Rep, 2018)
Therapeutic applications of mesenchymal stem cells (MSCs) are limited due to their early death within the first few days of transplantation. Therefore, to improve the efficacy of cell-based therapies, it is necessary to manipulate MSCs so that they can resist various stresses imposed by the microenvironment. Moreover, the role of superoxide dismutase 3 (SOD3) in regulating such survival under different stress conditions remain elusive. In this study, we overexpressed SOD3 in MSCs (SOD3-MSCs) and evaluated its effect under serum starvation conditions. Nutritional limitation can decrease the survival rate of transplanted MSCs and thus can reduce their efficacy during therapy. Interestingly, we found that SOD3-MSCs exhibited reduced reactive oxygen species levels and greater survival rates than normal MSCs under serum-deprived conditions. In addition, overexpression of SOD3 attenuated starvation-induced apoptosis with increased autophagy in MSCs. Moreover, we have demonstrated that SOD3 protects MSCs against the negative effects of serum deprivation via modulation of AMP-activated protein kinase/sirtulin 1, extracellular signal-regulated kinase activation, and promoted Forkhead box O3a trafficking to the nucleus. Taken together, these results demonstrate that SOD3 promotes MSCs survival and add further evidence to the concept that SOD3-MSCs may be a potential therapeutic agent with better outcomes than normal MSCs for various diseases involving oxidative stress and compromised MSCs survival during therapy.